Anggaran - Gumilang, Inda; Pratama, Aditia (Jurnal Manajemen Retail, 2023)
Research on decentralization and budget participation on managerial performance recently is a field of research thatmany have debates, thus attracting the interest of researchers to conduct further studies of the influence. Thepopulation in this study is the manager of the Company's manufacturing industry with purposive samplingsampling techniques. The analysis tool to test the hypothesis using simple regression analysis.Research generatesDecentralization positive and significant impact on Managerial Performance. meaning that the higher thedecentralization of the motivation of the manager with the unmet need for self-actualization. Participation Budgetnegative and significant effect on Managerial Performance. This means that in the preparation of the budgetinvolved some employees may of them have properties that are less concerned about the budget so that is lesscooperative.